Correlation of Serum Anti-Clq Antibody Levels and Disease Activity in Patients with Systemic Lupus Erythematosus - Ferdy Ferdian; Riardi Pramudiyo; Laniyati Hamijoyo (Indonesian Rheumatology Association, 2019)
Background. Antibody to complement C1q (Anti-C1q Antibody) can be found in Systemic Lupus Erythematosus (SLE) patients. Complement C1q plays a role in the clearance of apoptotic cells and immune complexes. Anti-C1q causes complement C1q become inactive so that the clearance decreases, which induces self antigen and inflammatory response. Many tissue inflammation are associated with disease activity and lupus manifestations. The aim of this study is to find out the correlation of anti-C1q level with disease activity, so that anti-C1q can be used as an objective indicator of inflammation along with SELENA-SLEDAI. Method. This is an analytic descriptive study with cross sectional design. Anti-C1q antibody levels were measured in 52 SLE patients who are hospitalized or treated routinely in outpatient clinic of Rheumatology Dr.Hasan Sadikin Hospital Bandung Indonesia from October to December 2015. Result. Most of the study subjects were women (94%), with a median age of 33 years. There were 13 new patients (25%), and the rest 42 patients were treated routinely. The median SELENA-SLEDAI was 6 (0-32). Subject were divided into no activity (11.5%), low disease activity (34.6%), medium disease activity (25%) high disease activity (15.4%) and very high disease activity (13.5%). Median anti-C1q level was 3.92 U/mL (range 0.6-100.2 U/mL). Anti-C1q antibody levels were positively correlated with SLE disease activity based on SELENA-SLEDAI scores (r=+0.304; p=0.014) Conclusion. Anti-C1q antibody levels has mild correlated with lupus disease activity based on SELENA-SLEDAI score Keywords : Anti-C1q antibody, SLE, SELENA-SLEDAI.